Imaging modes for scanning confocal electron microscopy in a double aberration-corrected transmission electron microscope. - Nellist, P; Cosgriff, E; Behan, G; Kirkland, A (2008)
Aberration correction leads to reduced focal depth of field in the electron microscope. This reduced depth of field can be exploited to probe specific depths within a sample, a process known as optical sectioning. An electron microscope fitted with aberration correctors for both the pre- and postspecimen optics can be used in a confocal mode that provides improved depth resolution and selectivity over optical sectioning in the scanning transmission electron microscope (STEM). In this article we survey the coherent and incoherent imaging modes that are likely to be used in scanning confocal electron microscopy (SCEM) and provide simple expressions to describe the images that result. Calculations compare the depth response of SCEM to optical sectioning in the STEM. The depth resolution in a crystalline matrix is also explored by performing a Bloch wave calculation for the SCEM geometry in which the pre- and postspecimen optics are defocused away from their confocal conditions.